Social entrepreneurship : - Bornstein, David (Oxford University Press, 2010)
In development circles, there is now widespread consensus that social entrepreneurs represent a far better mechanism to respond to needs than we have ever had before--a decentralized and emergent force that remains our best hope for solutions that can keep pace with our problems and create a more peaceful world.